FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DEDICADA A LA ELABORACIÓN Y COMERCIALIZACIÓN DE CERA DEPILADORA A BASE DE AZÚCAR PARA MUJERES EN LA CIUDAD DE LOJA - Loján Poma, Judith Abigail (2017)
The present project has the purpose of presenting a proposal for the implementation of a company dedicated to the elaboration and commercialization of sugar-based hair removal wax for women in the city of Loja, under this context arises the need to cover the taste and preference of The existing local population that demand the whole city of this product as part of the demands of a changing market where the customer is an important entity for the development of economic and productive components. The general objective of this study is to carry out a feasibility study for the creation of a company dedicated to the elaboration and commercialization of sugar-based waxing wax for women in the city of Loja, based on the following studies: Market, Technical , Economic-Financial and Financial Assessment The methodology used is based on the achievement of the objectives of the project, the use of methods and techniques allowed us to collect accurate information to determine what our potential applicants. In the market study, the information obtained from the study population is detailed through the use of primary data sources; The same ones that are described in the respective tables and statistical graphs with their respective analysis that allowed to know the preferences of the consumer and the characteristics of the market in terms of supply and demand, obtaining the demand unsatisfied, for this was used the values of the 6 Economic Population Active in 2016 with a total of 38,684 women giving a total of 381 surveys. The Technical Study determined the size and location of the company, which will be located in the city of Loja, Cantón Loja, Punzara parish, Barrio Época, Av. Los Paltas and Provides the conditions and all the basic services for its execution. The Installed Capacity of the company will be 175,200 units of wax epilator of 125gr each, while in the Used Capacity will be 41,600 units of wax epilator of 125gr each, which is considered prudent to start during the first five years. In the study of the legal administrative structure of the company were determined some legal aspects that is required for normal operation such as: the type of company, its hierarchical levels and function manuals. Within the Financial Study, an initial investment of US $ 20,517.62 was established, which will be financed by BanEcuador, whose amount is US $ 7,000 equivalent to 34.12% of the investment, with an annual effective interest rate of 11%; While 65.88% will be contributed by the investor with an amount of 13,517.62. The financial results show the following results: Net Present Value (NPV) is $ 35.056,14; The Internal Rate of Return (IRR) is 60.66%; In the Sensitivity Analysis indicates that the project supports a 6,51% increase in costs, so the project is feasible, yielding a result that the project supports a decrease in revenue of 5.80% for which the project is feasible, Ratio Cost Benefit shows us that for each dollar invested we would get a profit of $ 0.12 ctv, ie our benefit / cost ratio is greater than 1, The project investment recovery period will be 1 year 11 months and 24 days , With this result it is concluded that the project is approved. And finally, based on all the studies, their respective conclusions and recommendations are presented.